Promoter architecture and transcriptional regulation of musculoskeletal embryonic nuclear protein 1b (mustn1b) gene in zebrafish. Issue 12 (4th October 2017) - Suarez‐Bregua, Paula; Chien, Chien‐ju; Megias, Manuel; Du, Shaojun; Rotllant, Josep
Abstract : Background: Mustn1 is a specific musculoskeletal protein that plays a critical role in myogenesis and chondrogenesis in vertebrates. Whole‐mount in situ hybridization revealed that mustn1b mRNAs are specifically expressed in skeletal and cardiac muscles in Zebrafish embryos. However, the precise function and the regulatory elements required for its muscle‐specific expression are largely unknown.Results: The purpose of this study was to explore and uncover the target genomic regions that regulate mustn1b gene expression by in vivo functional characterization of the mustn1b promoter. We report here stable expression analyses of eGFP from fluorescent transgenic reporter Zebrafish line containing a 0.8kb _mustn1b‐Tol2‐eGFP construct. eGFP expression was specifically found in the skeletal and cardiac muscle tissues. We show that reporter Zebrafish lines generated replicate the endogenous mustn1b expression pattern in early Zebrafish embryos. Specific site directed‐mutagenesis analysis revealed that promoter activity resides in two annotated genomic regulatory regions, each one corresponding to a specific functional transcription factor binding site.Conclusions: Our data indicate that mustn1b is specifically expressed in skeletal and cardiac muscle tissues and its muscle specificity is controlled by the 0.2‐kb promoter and flanking sequences and in vivo regulated by the action of two sequence‐specific families of transcription factors. Developmental Dynamics 246:992–1000, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: The genomic structure of the mustn1b locus in zebrafish appeared to be highly conserved to that in mammals. Expression of mustn1b:eGFP in skeletal and cardiac muscles of zebrafish confirm the muscle‐specific pattern conserved across vertebrates. Reporter transgenic embryos reveal eGFP localization in slow and fast‐twitch myofibers. Myod and Mef2 cis‐acting regulatory elements govern the mustn1b promoter for skeletal and cardiac muscle expression, respectively.